P703 Clinical, radiographic and endoscopic remission with vedolizumab treatment in Crohn's disease. (16th January 2018) - Kotze, P G; Ma, C; Almutairdi, A; Al-Damarki, A; Devlin, S; Kaplan, G; Seow, C; Novak, K; Lu, C; Ferraz, J; Stewart, M; Buresi, M; et al.
Abstract: Background: Vedolizumab (VDZ) is a gut-specific α-4-β-7 integrin antagonist that has demonstrated efficacy in randomised controlled trials to induce and maintain clinical response and remission in moderate-to-severe Crohn's disease (CD) randomised controlled trials. The aim of this study was to evaluate the symptomatic and objective response and remission rates achieved with VDZ therapy in CD in a large tertiary care cohort. Methods: A retrospective cohort study was performed at the University of Calgary with adult (≥18 years) CD patients receiving VDZ induction between 2012 and 2017. The primary outcome was clinical or objective remission at 3, 6, and 12 months after induction. Clinical remission was defined by complete absence of symptoms and no need for corticosteroids. Objective remission was defined by steroid-free endoscopic mucosal healing or complete normalisation of radiographic appearance on contrast-enhanced ultrasound or CT/MR enterography. Results: A total of 122 patients were included. Mean follow-up was 43.4 weeks (SD 30.8 weeks). Sixty-nine percent (84/122) of patients had previously failed anti-TNF therapy; 18.9% (23/122) had failed at least 3 previous biologic therapies. Steroid-free clinical remission at 3, 6 and 12 months was 19.8% (22/111), 22.1% (21/95), and 22.1% (15/68), respectively. Steroid-free endoscopic or radiographic remission occurred in 11.5% (6/52), 21.2% (14/66), and 18.9% (7/37) patients at 3, 6, and 12 months, respectively. Mucosal healing on endoscopy was achieved by 22.2% (6/27), 33.3% (14/42), and 25.9% (7/27) of patients at 3, 6, and 12 months, respectively. 109 CD patients with symptomatic response within 6 months to VDZ induction therapy were followed for a mean duration of 46.3 weeks (SD ± 31.3 weeks). Composite loss of response occurred in 36 patients (33.0%) in follow-up at a mean time of 35.2 weeks (± 20.9 weeks). Adverse events (AE) were reported in 35 patients (28.7%). The most common AE were infections (16/122, 6.6%) and infusion reactions (8/122, 6.6%). Serious adverse events were reported in 8 patients (6.6%). Two deaths occurred in the cohort: one patient developed cholangiocarcinoma (pre-existing primary sclerosing cholangitis) and a second patient died from metastatic renal cell carcinoma (diagnosed prior to initiation of VDZ). Conclusions: In this cohort of patients with highly refractory CD, VDZ was effective for inducing steroid-free clinical, endoscopic, and radiographic remission. Loss of response to VDZ occurred in one-third of patients and approximately 20% will discontinue treatment.